Hemolytic anemia in a 2-years old caused by Glucose 6 Phosphate Dehydrogenase Deficiency (G6PD): a case report - Paulus Arief Budiman; Ketut Ariawati; Anak Agung Ngurah Ketut Putra Widnyana (Intisari Sains Medis, 2021)
Background: Glucose-6-Phosphate-Dehydrogenase (G6PD) deficiency is an enzyme abnormality related to sex chromosomes (x-linked), which is inherited. The activity or stability of the G6PD enzyme decreases, thus causing the breakdown of red blood cells when an individual is exposed to exogenous substances that can cause oxidative damage. This case study aims to describe a rare case of hemolytic anemia caused by glucose 6 phosphate dehydrogenase deficiency in a two-year-old boy. Case Presentation: A two-year-old boy presented with agitated, pale, yellowish eyes and body and projectile vomiting after consuming fava beans. He had a prior history of packed red cell transfusion. Physical examination found the conjunctivae were pale with the icteric sclera. Laboratory examination revealed leukocytosis, moderate normochromic normocytic anemia, increased reticulocytes count, and elevated total and unconjugated bilirubin. Peripheral blood smear examination found microcytes, spherocytes, fragmentocytes, and burr cells. Coomb test was negative with decreased G6PD result. Conclusion: G6PD deficient patients have no symptoms until exposed to oxidizing drugs, infections or after fava beans ingestion which may cause hemolytic anemia and jaundice. Several methods of screening and diagnosis of G6PD can be performed to avoid morbidity and mortality.